Beyond gamification: sociometric technologies that encourage reflection before behavior change - Belim, Vítor; Lyra, Olga; Teixeira, Pedro; Caraban, Ana; Ferreira, Maria José; Gouveia, Rúben; Lucero, Andrés; Karapanos, Evangelos (My University, 2014)
Gamification, the use of game design elements, such as points, levels, badges and achievements, in non-game contexts is a promising approach for encouraging desired behaviors. In this paper we describe our design process and early evaluation of a prototype that sensed children's social interactions (i.e., physical proximity) in the playground, and attempted to encourage pro-social behaviors through motivational feedback on a public display. We illustrate how we came to realize the potentially detrimental effect of gamification on children's intrinsic motivation and depth of reflection, and how we attempted to circumvent this through encouraging empathic understanding on children regarding the consequences of their behaviors on others.
Keywords: Children; Gamification; Persuasive sociometric technologies